A versatile and low-toxicity material for photothermal therapy in deeper tissues. Issue 31 (28th July 2021) - Jin, Liguo; Wang, Yinyin; Ouyang, Huan; Liu, Yu; Zhu, Zhenling; Wang, Shuhua; Xin, Hongbo; Wang, Xiaolei
Abstract : As a proof of concept, we demonstrate the regulative effect of external NIR defined TPUU on intestinal flora. The result implies that TPUU can go beyond the realm of ordinary photosensitizers to realize therapeutic effect in deeper tissues. Abstract : The limited depth of the near infrared (NIR) response is one of the major flaws of the present photothermal therapy (PTT). In this article, thermosensitive polyurethane urea (TPUU) was synthesized by polymerization. Subsequent experiments showed that, compared with classical photosensitizers, TPUU has higher photothermal effects and lower cytotoxicity. These valuable properties could make the present PTT research provide more therapeutic options among different tissues and organs. As a practical example, TPUU was applied to regulate the intestinal flora through external NIR irradiation, which implied its promising expanded applications in deeper tissues.